Religionspädagogisches Kompendium - Rothgangel, Martin; Adam, Gottfried; Lachmann, Rainer (Vandenhoeck & Ruprecht, 2013)
This volume is a traditional portrait of the basics of religious education and provides as well an overview of the present state of the art of pedagogical and didactic theories in the teaching of religion.In its now 7th and completely revised edition this compendium also offers the theoretical and structural background for many practical suggestions for transferring this knowledge in the classroom. It provides information on the central themes surrounding the Bible, church history, theology, dogmatics, ethics and ecumenical matters.